2017
DOI: 10.1007/s12602-017-9344-0
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Activity of Lactobacillus pentosus ŁOCK 0979 in the Presence of Polyols and Galactosyl-Polyols

Abstract: The antifungal activity of Lactobacillus pentosus ŁOCK 0979 depends both on the culture medium and on the fungal species. In the control medium, the strain exhibited limited antagonistic activity against indicator food-borne molds and yeasts. However, the supplementation of the bacterial culture medium with polyols (erythritol, lactitol, maltitol, mannitol, sorbitol, xylitol) or their galactosyl derivatives (gal-erythritol, gal-sorbitol, gal-xylitol) enhanced the antifungal properties of Lactobacillus pentosus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 26 publications
(30 reference statements)
1
13
0
Order By: Relevance
“…Lactobacilli also produce inorganic compounds, such as hydrogen peroxide [96], leading to oxidative stress and genotoxicity in higher amounts. These compounds display broad antimicrobial activity against bacteria and fungi [97][98][99][100]. Current knowledge on specific Lactobacillus-produced metabolites and their respective anticandidal mechanisms is summarized in Table 1.…”
Section: Direct Antifungal Activitymentioning
confidence: 99%
“…Lactobacilli also produce inorganic compounds, such as hydrogen peroxide [96], leading to oxidative stress and genotoxicity in higher amounts. These compounds display broad antimicrobial activity against bacteria and fungi [97][98][99][100]. Current knowledge on specific Lactobacillus-produced metabolites and their respective anticandidal mechanisms is summarized in Table 1.…”
Section: Direct Antifungal Activitymentioning
confidence: 99%
“…Lategan et al [31] isolated Aeromonas media (strain A199) from eel (Anguilla australis) culture water and were observed to have a strong inhibitory activity against Saprolegnia sp. Lipińska et al [32] reported antifungal activity of Lactobacillus pentosus in the presence specific media.…”
Section: Antifungal Activitymentioning
confidence: 99%
“…However, there has been little research on the use of Lactobacillus pentosus to treat IBD induced by DSS. L. pentosus has been shown to have antifungal activity and inhibit the growth of pathogenic microorganisms (Lipińska et al, 2018). Other studies have shown that L. pentosus has a therapeutic effect on Salmonella-infected mice and it inhibits the growth of Salmonella, inhibits the damage caused by the invasion of intestinal epithelial cells, and improves the host's immune function (Liu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%